Stereotactic body radiation therapy versus no treatment for early stage non–small cell lung cancer in medically inoperable elderly patients: A National Cancer Data Base analysis. Issue 23 (8th September 2015) - Nanda, Ronica H.; Liu, Yuan; Gillespie, Theresa W.; Mikell, John L.; Ramalingam, Suresh S.; Fernandez, Felix G.; Curran, Walter J.; Lipscomb, Joseph; Higgins, Kristin A.
Abstract : BACKGROUND: Stereotactic body radiation therapy (SBRT) has demonstrated high rates of local control with low morbidity and has now emerged as the standard of care for medically inoperable, early stage non–small cell lung cancer (NSCLC). However, the impact of lung SBRT on survival in the elderly population is less clear given competing comorbid conditions. An analysis of the National Cancer Data Base (NCDB) was undertaken to determine whether definitive SBRT improves survival relative to observation alone patients ages 70 years and older. METHODS: The NCDB, a retrospective national database that captures approximately 70% of all patients treated for cancer, was queried for patients aged 70 years or older with early stage (T1‐T3N0M0) NSCLC from 2003 to 2006. Overall survival was compared between patients who received stereotactic body radiotherapy alone and those who received no treatment. An extended Cox proportional hazards model was applied to estimate the treatment effect of SBRT. RESULTS: In total, 3147 patients met the selection criteria for this analysis. SBRT was delivered to 258 patients (8.2%), and 2889 patients (91.8%) received no treatment. There was no significant difference in the distribution of Charlson/Deyo comorbidity index scores between the 2 groups ( P = .076). Multivariable analysis revealed improved overall survival with SBRT compared with observation for the entire cohort (hazard ratio, 0.64; P < .001). CONCLUSIONS: SBRT is associated with improved survival in elderly patients with early stage NSCLC who have concurrent comorbid conditions compared with observation alone. The current data support the use of SBRT for the treatment of elderly patients with early stage NSCLC who have limiting comorbid conditions. Cancer 2015;121:4222–4230. © 2015 American Cancer Society . Abstract : Medically inoperable elderly patients with early stage non–small cell lung cancer are often recommended observation and supportive care only. However, the current findings suggest that these patients should be offered stereotactic body radiation therapy, because it appears to improve their survival compared with no treatment for all patients aged 70 years and older.